Comparison of polyglycolic acid suture and cyanoacrylate glue for the repair of urethral incision in male goats - Singh, Tarunbir; Amarpal, Amarpal; Kinjavdekar, P; Aithal, H; Pawde, A M; Pratap, K (The Indian Journal of Animal Sciences, 2007)
The study was carried out on 12 male goats aged 6-9 months, weighing 10-15 kg, divided into 4 groups (n=3), to evaluate the suitability of polyglycolic acid (PGA) suture, cyanoacrylate glue (CA) and their combination for the repair of urethral incision. Post-scrota1 urethrotomy was performed under lumbosacral epidural analgesia and urethral incision was closed using PGA suture in group 1, CA in group 2 and combination of both in group 3. In control animals of group 4, urethra was left unsutured after putting an indwelling catheter. The animals were observed for clinical, haematological, biochemical and radiographic parameters. Mild to moderate pain and swelling at the incision site were observed for 1 week in the animals of treatment and 2 weeks in control animals. Leakage of urine from the incision site and significant leukocytosis characterized by neutrophilia and lymphocytopaenia, increase in aspartate amino transferase, alanine amino transferase and alkaline phosphatase, blood urea nitrogen (BUN) and creatinine were observed in control animals. Plasma glucose increased significantly for short period post-operatively in all the treatment groups and for more than 2 weeks in control group. Contrast urethrograms showed complete urethral healing in the animal of all treatment groups. It was concluded that both PGA suture and CA glue when used alone are equally effective in the repair of urethral incision in goats.